Вы находитесь на странице: 1из 37

-

:
: -263
: . .

2003

2
1.

3
2.

4
2.1.

4
2.2.

4
2.3.

5
2.4.

6
2.5.

6
2.6.
7
2.7.

8
2

2.7.1.

8
2.7.2.

9
2.7.3.

9
2.7.4. .

10
2.7.5.

12
2.7.6.

n-

13
2.7.7.

14
2.7.8.

15
3.
16
3.1.

16
3

3.2.

18
3.3.

18
3.4.

19
3.5.

19
3.6.
20
3.7.

21
3.8.
22
3.9.
22

24

1.

,
.


. ,
,

.

, .
,
.
(, .
.), (, . .). ,
,
.
g(t), x(t).
,
.

,
.

: . ,

y (.1).
,
. , ,
, J.
, .
:
J = k (t ) + m(t ),

k (t) ; m(t) ,
. J b=k/J, (t)=m(t)/J,
(t) u(t),
= bu (t ) + (t ).


x1 = , x 2 = = x 1


x 1 = x 2 ; x 2 = bu (t ) + (t ),


x1 0 1 x1 0
0
x = 0 0 x + b u (t ) + 1 (t ).
2

2

-
x 0 1 0 0
x = 1 ; F =
; G = b ; = 1,
0 0


x2

x = Fx (t ) + Gu (t ) + (t ).

2.
2.1.
, ,
, ,
.

,
,
.

n- .
x=x(t),
t, , ,
.
, n-
x(n).
x(n):
x=x(t) . x(t)
t.
(t,x) x=x(t) ,
.
x=x(t,C)
,
.

2.2.

n x1,, xn .

,
. :


. ,
.

()

.
:

G n
8

xi=xi(t), G ,

G.
- t,
().
2.3.

, G,
t0, :

t0, xi0 (i=1, 2,, n)


x1(t), , xn(t), .
(n+1)- t, x1,, xn,
n xi=xi(t) n-
. t0, x10,, xn0
.
2.4.


(1)
(1) G n
xi=xi(t,c1,,cn), i=1,2,,n. , f(t,x1,
,xn) G x1,
,xn, L>0,
(t,x1,,xn) (t, xs1,,xsn), G,

f (t , x1 ,..., x n ) f (t , x s1 ,..., x sn ) L xi x si
i =1

(1) fi(t, x) t
x1,,xn G.
xi=xi(t), I=1,2,n (1),
xi(t0)=xi0,
K, t0.
K,
t0. ,
K G.
f(t, x1, ..., n) xi
G, .
2.5. -

(2)
,
.

n z1(t), ..., zn(t) -


(2) ,
'
, - z i (t )

z i' f i (t , z1 (t ),..., z n (t ))

(i = 1,2,..., n)

tK,
10

.
(t0, x10, , n0) fi(t,
xi,...,n) t G
t, x1, 2, ..., n. ,
fi(t, x1,..., n)
t, x1,..., n G. fi (t, x1,...,
n) G .
, >0 >0, ,


- (2).
G , ( n=1
. 2, ). (t, xlo, ...,
n0)

. (t1, x11,..., xn1).

;
(t2, x12,..., xn2),
.
xi=xi(t) (i=l, 2, ..., n),
.
- .
G.
xi(t) (i=l, 2, ..., n) (2),
. si(t) (i=1, 2, ..., n) -
(1) .

x (t ) s (t ) L (e
i =1

nL ( t t 0 )

1).

, |tt0|<h,
n

i =1

xi (t ) si (t )

nLh
e nLh 1
(e 1) = k , k =
L
L

, 0 xi(t) (i=1, 2, ..., n)


si(t) (i=l, 2, ..., n) , (t0, xi(t0)),
11

.
-.


.
2.6.

(2),
fi(t, xl ,..., n) t
1, ..., n G.
x=x(t, t0, x0) ,
. , |t-t0|
h. >0 (, h)>0,
x=s(t, t0, z0),
s (t , t 0 , z 0 ) = z 0 ,

||x0z0||<, |t-t0|h

|| x(t , t 0 , x 0 ) s(t , t 0 , z 0 ) ||<

(1,, s)= , fi(t, x, )


t, x1, , xn, 1, ,
s G n+s+1-
x1, , xn L.
x=x(t, ) =,
x(t0, )=x0
.
:
12

x(t, )
=, x(t0, )=x0.
>0 (, h)>0, |
|<, x(t, ) |tt0|h

|| x(t, )x(t, ) ||<.

.

() .
,
,

.
2.7.
2.7.1.


,
.

(1)
13


[1 ,b1](, b), (a, b) - ,
aik(t) fi(t) .
2.7.2.
(1) , fi(t) 0 (i=1, 2, , n).

(3)
S {x(t)}
n, .

z (t ) = c1 x1 (t ) + c 2 x 2 (t ) + ... + n x n (t ), (4)
c1, c2, , cn . ,
(4).
(4) (3).
n - (3),
S, .
2.7.3. .
n

, , ,
. ,

x1(t), ..., n(t) -,


W(t)=0.
- x1(t), ..., xn(t) n
(3). , W(t)
14

- t0[, b], W(t)


[, b].
: -

t = 0 W(0) = 0, W(t) 0. ,
- 1(t) x2(t)
(3) ,
, t=0.
t
,
.
x1(t), x2(t), ..., xn(t) n (3).
W(t) t0 t
:

A(t).
2.7.4. .

(2)
(3)
x=(t) (t) (2).
(t)= (t) (t)
(3).
(2)

ci ; i(t) (i=1, 2, , n)
15

(3).
(2)
. . 1(t), 2(t), , n(t)
(3).
(2)

, ci , t.
(2):
- i(t) (3),


i(t) (i=l, 2, ,..., n).

. ,
i(t)=i(t) (i=l, 2,..., n).
:
,
,

2.7.5.



.

16

(2),

(3)
1, 2, , n
(3). X1(t),
:

1(t)

. t[a, b]. ,
X-11(t) t[, b].
X(t, t0) = X1(t)X1-1(t0)

(3). , X(t,

t0)=

X(t, t0) (3).


(t) (3),
(t0)=x0,
, ,
,

x(t)

x(t0)=x0,

X(t, t0) (3):

, , . .

17

(2),


x(t),
x(t0)=x0,
X (f) ,
xt'=, X (t0) = E.
2.7.6. n-
n-

a0(t), , an(t) t(a, b),


0(t) 0.

18

(t)
.
i'(t) :


1 ,, n, W(t) 0,
. c'i(t),
ci(t)

x(t) ,
,

ci()

19

1, , n
.

c1(),

cn().

, x1(t, ) .
2.7.7.

n-

y ( n ) + a n 1 y ( n 1) + ... + a1 y '+ a 0 y = 0

(5)

y=ekx. y=kekx, y=k2ekx, ,


y(n)=knekx.

(5):
knekx++a2k2ekx+a1kekx+a0ekx=0
, ekx, x
, :
kn++a2k2+a1k+a0=0
k, n ,
, .

:
1.

ki, , kj

. km
: ym=cmekmx.
20

2.

ki,, k2j .
km;m+1=am bmi
ym=cmeamxcos(bmx); ym+1=eamxsin(bmx).

3.


ki m.
:

yi=ciekix,

yi+1=xci+1ekix,

yi+m=xm-

1ci+mekix.
4.

2
ki;i+1=ai bii m.

yi+1=ci+1eaixsin(bix);

yi=cieaixcos(bix);

yi+2=xci+2eaixcos(bix)

yi+3=xci+3eaixsin(bix) ; ; yi+m=x2m-1cieaixcos(bix);

yi+m=x2m-1
ci+1eaixsin(bix).

, , {y(x)}
n,
- . ,

. ,
n- (5)

, ( )
.
2.7.8.

y(n)+Pn-1(x)y(n-1)++P2y+P1y+P0=f(x), (6)
P0(x), P1(x),, Pn-1(x), f(x) ,


21

x.

y(n)+Pn-1(x)y(n-1)++P2y+P1y+P0=0,

(7).

(6) y(x)

y=c1y1+c2y2++cnyn,

(6) y
(7)
yc: y=yc+y.

.
.
f(x).
f(x).
f(x):
1. f(x)=P(x)eax, P(x) .
:
1) y=xmQ(x)eax,

m-

;
2) y=Q(x)eax, a
,
Q(x) , P(x),
.
2. f(x)=(Pn(x)cos(bx)+Lm(x)sin(bx))eax, Pn(x) Lm(x)
. :
1) y=(Mn(x)cos(bx)+Nn(x)sin(bx))eax, (a bi)
;
2) y=xm(Mn(x)cos(bx)+Nn(x)sin(bx))eax, (a bi) m-
,
Mn(x) Nn(x) ,
Pn(x) Lm(x).

22

,
,
, , x,
x2, x3cos(bx) . .

23

3.

3.1.


. , .

.

,
(1)


(2)
(1) x=const g=const.


, ,

24


.
, ,
,

,
x=(g)
x=ag+b.
x=y(g) ,
,
g
. x=(g) ,
(0, g0),
(. 3).

, x=(g)
.
,

,

.
25


.
(1).
(2). g0 0
. g
=0+x, g=g0+g, g x g
x . (1)
(0,
0, 0, g0):

,
g x .

, F(x", x', x, g)
g0 0.
g, ,
, F(x", x', x, g)

,
, g ,
.

,
F(x", x', x, g) ,
.
26

(1)
(0, 0, 0, g0).
F(x", x', x, g) , . .
(0, 0, 0, g0). ,


. ,

F(x", x', x, g) ,
.
(1)
(0, 0, 0, g0).
F(x", x', x, g) , . .
(0, 0, 0, g0). ,


.
3.2.

, ,
:
1) mi,
, , ,
;
2) ,
yj, ,
;
3)

()

xk,
.
mi, yj xk .

,
,
27

:
m1

m 2
m=
;
...

ml

y1
x1
y

2 x2
y=
; x=
...
...


xn .
y p

, m
t, . ,
y t,
. ,
x t, .
3.3.

t
x(t0) m(t0, t),
x(t)=F[x(t0); m(t0; t)],
F .
t x(t0) m(t0; t)
y(t)=z[x(t0); m(t0; t)].
.
, ,
:
x(t)=F[x(t); m(t)],
y(t)=z[x(t); m(t)].
.

, :
dx(t)/dt=A(t)x(t)+D(t)m(t);
y(t)=B(t)x(t)+G(t)m(t),
28

A(t) ; D(t) ; B(t)


; G(t) .

x(t)=p(tt0)C1(t), (7)
p(tt0)=exp A(tt0) , 1(t) ,
, x0
.
t,
dx(t)/dt=Ax(t)+p(tt0)dC1(t)/dt.
(7) ,

.
Dm(t)=p(tt0)dC1(t)/dt.
1(t),
t 1

C1 = p ( t 0 ) Dm( )d
t0


(7)
t

x (t ) = p (t t 0 )C 2 + p (t ) Dm( ) d
t0

t=t0, p(tt0)=I 2=x(t0).


t

x (t ) = p (t t 0 ) x (t 0 ) + p (t ) Dm( )d
t0

3.4.


, :
29

dv(t)/dt=Av(t),

v(t)

-,

mi xk
m
v = .
x


, ,
v
.
3.5.

:
y(t)=Bx(t)+Gm(t), (8)
y p- , ; B
pxn; G pxr.
B
b11
b
21
B=
...

b p1

b12
b22
...
bp2

... b1n
... b2 n
... ...

... b pn

G
g11
g
21
G=
...

g p1

g12
g 22
...
g p2

... g1r
... g 2 r
... ...

... g pr

, (8), p
r

y i (t) = b ik x k (t) + g ij m j (t), i = 1,2,..., p


k =1

(9)

,
30


. (9) , xk

y1, y2, , yi, , yp,
bik i=1, 2, , p . , xk
, k-
. , xk
. ,
, B ,
.
3.6.


dx(t)/dt=Ax(t)+Dm(t),

(10)

x n- ; m r- ,
; A
n- ; D nxr.
A (
)
2
0
= T 1 AT =
...

0
2
...
0

... 0
... 0
... ...

... n

A,
.
x=Tz,

dz(t)/dt=z(t)+m(t),
31

=T-1D=[ij]nxr.
z
. ,
i
, i , T , ,
.
,
:
r

z i (t ) = i zi (t ) + ik mk (t ), i = 1,..., n
k =1

, mk
- zj,
r

k =1

jk

mk (t ) = 0

jk=0 k=1, 2, , r. ,
j- . ,

, .

. ,

.

: , (10),
, ,
; , ,
32

.
3.7.

y(t) r(t):

, p=d/dt,
F(t)=B(p)v(t), , ,
.
.
A(p) , M(p)
.
.
() D()
W() ,



.
3.8.

Lij=anijpn+a(n-1)ijpn-1+

+a1ijp1+a0ij. (
,
33

Lij p, ,
:
(p) , :

, ki- .

34

3.9.

,
:

p=d/dt.

(11)
y,
px1
y

y, py, , pn-1y (11)


pny,
ai bi:

i , -,

, bi ,
. ,
A, B, C, D

35

36

:
1. . .
2. . . .

37

Оценить